Ireland : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that GDP growth of Ireland declined to almost 6 percent in 2001 from 11 1\2 percent the year before, reflecting the global slowdown and the Information and Communications Technologies (ICT) shock as well as foot-and-mouth disease-related restrictions. The IMF's outlook is for GDP to rise by 3.2 percent in 2002, supported by steady growth in private consumption. Exports are projected to accelerate by midyear, although the recovery in private investment would take somewhat longer.